Tuning the balance between dispersion and entropy to design temperature-responsive flexible metal-organic frameworks - J. Wieme (Nature Portfolio, 2018)
Rational design of metal organic frameworks (MOFs) with shape-memory nanopores is a formidable challenge. Here the authors use an accurate theoretical approach to design thermo-responsive MOFs based on a balance of van der Waals and entropy contributions.